The Effect of Sleep Quality, Hot Work Climate, and Age on Work Fatigue Through Work Duration as an Intervening Variable on Charcoal Workers in Batam City - Noviyanti; Leni Utami; Ujang Amir; Raja Desti Rahma Pratiwi; Rifdah Wafiyana; Cut Putri Afsyarina Plangi Azza; Sherly Cahya Asyura; Jamal (Al-Hijrah Indonesia, 2026)
Workers in the informal charcoal industry face the risk of physical exposure and high workloads. This study aims to analyze the effects of sleep quality, hot work climate, and age on work fatigue, with work duration as an intervening variable, among charcoal workers in Batam City. This study used a quantitative, observational-analytical design. The population was charcoal workers; a sample of 99 workers was selected using a total sampling technique. Data were collected using a questionnaire and analyzed using Smart-PLS SEM. The results showed that sleep quality had a significant direct effect on work duration (coefficient = 0.591, p = 0.000) and work fatigue (coefficient = 0.618, p = 0.000). A hot work climate has a significant effect on work duration (coefficient = 0.264, p = 0.002). However, it does not have a significant direct effect on work fatigue (coefficient = 0.027, p = 0.354). Age has a significant direct effect on work duration (coefficient = 0.0395, p = 0.003) and work fatigue (coefficient = 0.431, p = 0.000). Work duration is significantly associated with work fatigue (coefficient = 0.431, p = 0.000) and fully mediates the relationship between hot work climate and work fatigue. The value indicates that the combination of variables in the model explains 96.5% of the variation in work fatigue. Sleep quality and work duration are the main determinants of work fatigue among charcoal workers. Hot work climates do not directly cause fatigue, but rather must first lead to an increase in workers' work duration. It is recommended that charcoal business owners arrange adequate rest periods between burnings and that workers maintain sleep quality to reduce the risk of chronic work fatigue. While previous studies examined these factors separately, the mediating role of work duration among informal charcoal workers remains under-investigated, which constitutes the research gap addressed here. Ethical approval was obtained prior to data collection, and informed consent was secured from all respondents.